PENERAPAN MIND MAPPING DALAM PEMBELAJARAN KETERAMPILAN BERBICARA PADA SISWA KELAS X MAN 1 MATARAM - Rabiyatul Adawiyah (MABASAN, 2016)
This research aims to describe the implementation of mind mapping strategy in learning speaking skill and get description of students` achievement before and after the implementation of mind mapping strategy. The learning process emphasizes the students to work cooperatively in small group to help each other in learning the material by using student centered. The method used is experimental study with two subjects that are X Mia 1 graders and X Mia 2 graders of  MAN 1 Mataram. The data collected through observation, questionnare, documentation, and interview. The result of this research show that the implementation of mind mapping strategy improve the students` achievement in learning speaking skill. It is shown by the difference of students` achievement between experimental class and control class which indeks by 8.438. numeral with windows SPSS analysis. Show that the numeral is significant on the believe of 99.99%. it is symbolize with 0,00 numeral in windows SPSS. In conclusion, there is the influence of mind mapping strategy in learning speaking skill.